2014
DOI: 10.2466/10.03.it.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Use of Translation in Learning English as a Foreign Language (EFL) among Bahrain University Students

Abstract: CITATION Al-Musawi, N. M. (2014)Strategic use of translation in learning English as a Foreign Language (EFL) among Bahrain university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 19 publications
4
37
0
4
Order By: Relevance
“…Çeviri, basit anlamda metni sadece yeniden yaratmak anlamına gelmemektedir, bilakis, hedef kültür içindeki bazı özelliklere dikkat ederek, içeriğin yeniden şekillendirilmesini de ifade eder. Bu nedenle, dilin semantik yapısı, belirli bağlamları ve işlevleri de vurgulanarak iletişimsel yetkinliğin geliştirilmesi için bir strateji olarak kullanılabilir (Al Musawi, 2014). Leonardi (2011), çevirinin yabancı dil öğrenimi sırasında kaçınılması mümkün olmayan "doğal olarak gerçekleşen" bir etkinlik olduğunu düşünmektedir; çünkü, öğrenciler diller arasında karşılaştırma yapmak için her zaman kendi dillerine başvurmaktadır.…”
Section: çEviri Ve Dil öğRetimiunclassified
“…Çeviri, basit anlamda metni sadece yeniden yaratmak anlamına gelmemektedir, bilakis, hedef kültür içindeki bazı özelliklere dikkat ederek, içeriğin yeniden şekillendirilmesini de ifade eder. Bu nedenle, dilin semantik yapısı, belirli bağlamları ve işlevleri de vurgulanarak iletişimsel yetkinliğin geliştirilmesi için bir strateji olarak kullanılabilir (Al Musawi, 2014). Leonardi (2011), çevirinin yabancı dil öğrenimi sırasında kaçınılması mümkün olmayan "doğal olarak gerçekleşen" bir etkinlik olduğunu düşünmektedir; çünkü, öğrenciler diller arasında karşılaştırma yapmak için her zaman kendi dillerine başvurmaktadır.…”
Section: çEviri Ve Dil öğRetimiunclassified
“…Naiman et al (1978) mendapati bahawa salah satu strategi yang sering digunakan oleh pelajar cemerlang bahasa ialah merujuk kepada bahasa ibunda (B1) (menterjemahkan) dan membuat perbandingan silang bahasa antara B1 dan bahasa sasarandalam pembelajaran bahasa ketiga. Kajian ini konsisten dengan beberapa kajian lain yang menunjukkan peranan terjemahan dalam pembelajaran bahasa dalam kalangan pelajar (Baddeley, 1990;Husain, 1995;Omura, 1996;Prince, 1996;Cohen & Brooks-Carson, 2001;Intan Safinaz, 2003;Elmgrab, 2012;Amin, 2013;al-Musawi, 2014;Camelia Petrescu, 2015;al-Hadithy, 2015).…”
Section: Pendahuluanunclassified
“…Melalui terjemahan, pelajar bahasa kedua dan ketiga berupaya menganalisis dan memahami struktur kompleks bahasa sasaran dengan cepat dan cekap (Chamot & Kupper, 1989;Oxford, 1990;Ts. Dilkova, 2010;al-Musawi, 2014). Kajian juga menunjukkan bahawa terjemahan digunakan dalam strategi memori, afektif, sosial dan tampungan untuk membantu pelajar mempelajari bahasa asing secara efisien melalui pelbagai saluran.…”
Section: Terjemahan Sebagai Strategi Pembelajaranunclassified
See 1 more Smart Citation
“…Students in early stages of learning the language are certainly exposed to some explanation in their mother tongue especially when explaining difficult grammar rules that the students cannot grasp in English (Al-Musawi, 2014). The studies conducted by Husain (1995), and Chia and Chia (2001) found that less proficient English learners more frequently employed or benefited from translation strategies than their counterparts who were more proficient learners of English.…”
Section: Introductionmentioning
confidence: 99%